The impacts of Covid-19 on poverty in Malaysia / Nor Azira Ismail - Ismail, Nor Azira (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2022)
The onset of the COVID-19 pandemic in 2020 has greatly impacted most of the nation including Malaysia. The recent data released by the Department of Statistics Malaysia (DOSM) has projected that the pandemic has reversed the decreasing trend on absolute poverty, causing it to increase to 8.4 percent (639,800 households) in 2020 compared to 5.6 percent (405,400 households) in 2019. Taking into account the data from household income to present the incidence of poverty, DOSM reported that the main sources of income of a household in 2020, which come from paid employment and self-employment recorded a decrease of negative 16.1 percent and negative 9.7 percent respectively. Meanwhile, the mean monthly household gross income decreased by negative 10.3 percent to a record RM7,089 as compared to RM7,901 in 2019. The reduction trend was contributed by households or individuals who experienced job losses, reduced working hours, and an increased in skill-related underemployment (Mahidin, 2021).